2013
DOI: 10.3389/fphys.2013.00253
|View full text |Cite
|
Sign up to set email alerts
|

Role of Per1 and the mineralocorticoid receptor in the coordinate regulation of αENaC in renal cortical collecting duct cells

Abstract: Renal function and blood pressure (BP) exhibit a circadian pattern of variation, but the molecular mechanism underlying this circadian regulation is not fully understood. We have previously shown that the circadian clock protein Per1 positively regulates the basal and aldosterone-mediated expression of the alpha subunit of the renal epithelial sodium channel (αENaC). The mechanism of this regulation has not been determined however. To further elucidate the mechanism of mineralocorticoid receptor (MR) and Per1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 34 publications
(46 reference statements)
1
20
0
Order By: Relevance
“…Chromatin Immunoprecipitation (ChIP)-mDCT15 cells were grown to ϳ80% confluence and then treated with vehicle (water) or 10 M PF670462 for 48 h. ChIP was performed using the ChIP-IT TM Express Enzymatic Kit (Active Motif) according to the manufacturer's instructions and as described previously (28). Chromatin concentrations were calculated, and equal amounts of vehicle-treated and 10 M PF670462-treated chromatin were used per pull-down.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin Immunoprecipitation (ChIP)-mDCT15 cells were grown to ϳ80% confluence and then treated with vehicle (water) or 10 M PF670462 for 48 h. ChIP was performed using the ChIP-IT TM Express Enzymatic Kit (Active Motif) according to the manufacturer's instructions and as described previously (28). Chromatin concentrations were calculated, and equal amounts of vehicle-treated and 10 M PF670462-treated chromatin were used per pull-down.…”
Section: Methodsmentioning
confidence: 99%
“…Per1 was found to positively regulate the expression of αENaC at baseline and after aldosterone stimulation in mouse CCD, OMCD and IMCD cells [8,71]. In the CCD, this regulation occurs through direct binding with an E-box domain on the αENaC promoter along with the mineralocorticoid receptor (MR) in the presence of aldosterone [71,72]. This direct regulation of αENaC by Per1 was also shown to be inhibited by Casein kinase 1δ/ε, a regulator of the core clock mechanism via phosphorylation of Per proteins and inhibition of Per1 nuclear translocation [73].…”
Section: Circadian Rhythms Along the Nephronmentioning
confidence: 99%
“…Aldosterone-mediated transcriptional regulation of the Scnn1a gene, encoding αENaC, occurs through the mineralocorticoid receptor (MR). PER1 appears to be involved in this regulation (Richards et al 2013d). In one of the first reports to link the molecular clock to renal sodium handling, Gumz and colleagues demonstrated that knockdown of PER1 in several renal CD cell lines resulted in decreased expression of αENaC (Gumz et al 2009).…”
Section: Per1 Action In the Kidneymentioning
confidence: 99%